2018
DOI: 10.3390/coatings8020080
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Xanthan Gum and Flaxseed Mucilage as Edible Coatings in Cheddar Cheese during Ripening

Abstract: The object of this study was to investigate the possibility of using xanthan gum and flaxseed mucilage as edible coatings for Cheddar cheese during ripening for 90 days. Five samples of Cheddar cheese blocks were coated with different coating materials in triplicate as follows: Coated with polyvinyl acetate as control (C), coated with 0.5% xanthan gum (XG), coated with 0.75% flaxseed mucilage (FM1), coated with 1% flaxseed mucilage (FM2), and coated with 1.25% flaxseed mucilage (FM3). All samples were kept at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 47 publications
(54 reference statements)
2
11
0
Order By: Relevance
“…The results showed that FFA production rate is increasing during storage, which is due to the lipolysis phenomenon. Milk fat hydrolysis which is called as lipolysis is a complex phenomenon which is the results of the activity of natural lipases of the milk, the lipolytic enzymes of the starter and non‐starter lactic acid bacteria, and lipases of the psychrotrophs during cheese manufacture and storage time (Soleimani‐Rambod, Zomorodi, Naghizadeh Raeisi, Khosrowshahi Asl, & Shahidi, ). The amounts of free fatty acids (FFA) were used as indicators of lipolysis in the cheese samples.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that FFA production rate is increasing during storage, which is due to the lipolysis phenomenon. Milk fat hydrolysis which is called as lipolysis is a complex phenomenon which is the results of the activity of natural lipases of the milk, the lipolytic enzymes of the starter and non‐starter lactic acid bacteria, and lipases of the psychrotrophs during cheese manufacture and storage time (Soleimani‐Rambod, Zomorodi, Naghizadeh Raeisi, Khosrowshahi Asl, & Shahidi, ). The amounts of free fatty acids (FFA) were used as indicators of lipolysis in the cheese samples.…”
Section: Resultsmentioning
confidence: 99%
“…several food-grade polymers have been discovered for nano and microencapsulation applications such as lipids, proteins, and carbohydrates. Furthermore, mucilage has a good ability to form a dense network after drying and their high molecular weight carbohydrate polymers make them suitable for nano and microencapsulation of food and bioactive compounds [ 102 ]. High molecular weights can aid in the retention of more key substances and increase stability.…”
Section: Application Of Mucilagementioning
confidence: 99%
“…Since the moisture content of samples were decrease throughout the maturation of Cheddar cheese, the fat content of Cheddar cheese was increase due to lipolysis, accompanied by a physicochemical process on Cheddar cheeses during maturation period (Soleimani-Rambod et al 2018 ). The evaluation of the overall acceptability’s curve and shape (Fig.…”
Section: Discussionmentioning
confidence: 99%